Deep Listening: Practicing Intellectual Humility in Geographic Fieldwork. Issue 1 (2nd January 2020) - Koch, Natalie
ABSTRACT: The political and ethical quandaries of the "crisis of representation" that beset the social sciences from the 1980s on continue to reverberate in how geographers conduct their research today. Illustrated with two vignettes from my research in the UAE and Kazakhstan, this article explores the idea of "deep listening" as a methodological tack and mindset to guide geographic fieldwork, rooted in intellectual humility. Deep listening involves a critical reflexivity about our subject positions as researchers, as well as a suspicion of metanarratives that prevail in the media and academic debates, and a willingness to question our complicity in reproducing those narratives through our choice of research topics and methods. Deep listening is ultimately a way of practicing intellectual humility - which involves accepting that we could be incorrect at many levels, whether theoretical, factual, emotional, social, cultural, or political, and seeking out opportunities to change our mind.